2017
DOI: 10.1016/j.msec.2016.12.074
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis, self-assembly and bioimaging applications of adenosine triphosphate containing amphiphilies with aggregation-induced emission feature

Abstract: Amphiphilic molecules with aggregation-induced emission (AIE) characteristics have attracted intensive interest for biological imaging applications for their self-assembly into nanostructures and obvious enhanced fluorescence intensity in aqueous solution. Although many AIE-active fluorescent organic nanoparticles (FONs) have been fabricated recently, the direct linkage of hydrophilic small molecules and hydrophobic AIE dyes has rarely been reported. In this work, we reported a one-pot strategy for preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…It is well known that aggregation, including self-assembly, causes fluorescence quenching of dye molecules in aqueous solution (it is sometimes termed “aggregation caused fluorescence quenching, ACQ”), owing to electron or energy transfer [40,41,42]. It occurs under relatively high concentrations for aggregation, at 10 µM or higher [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that aggregation, including self-assembly, causes fluorescence quenching of dye molecules in aqueous solution (it is sometimes termed “aggregation caused fluorescence quenching, ACQ”), owing to electron or energy transfer [40,41,42]. It occurs under relatively high concentrations for aggregation, at 10 µM or higher [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…[10] For traditional AIE polymers with big conjugated moiety, some of their drawbacks such as cumbersome synthesis, poor solubility, high cytotoxicity and so on need to be solved or overcome, which limits the use of biomaterials. [12][13][14] For the macromolecules without conjugated moiety, the amine, ester, carbonyl, amide and other groups can participate in the fluorescence emission process as chromophores, which generally do not emit light themselves or have a very low luminescence quantum yield. [15] However, it has been found that these non-conjugated polymers including the dendritic polyamides and hyperbranched polyamides can emit very strong fluorescence under appropriate condition.…”
Section: Introductionmentioning
confidence: 99%
“…proposed a theory of restriction of intramolecular motions (RIM), [4] which well explained AIE luminescence behavior of the traditional AIE‐polymers in different solid forms [10] . For traditional AIE polymers with big conjugated moiety, some of their drawbacks such as cumbersome synthesis, poor solubility, high cytotoxicity and so on need to be solved or overcome, which limits the use of biomaterials [12–14] …”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Further, depending upon the nature of hydrogen bonding, the proton transfer process can occur either inter or intramolecularly. Aggregation-induced emission (AIE), on the other hand, is an aberrant occurrence observed with particular molecular designs [9][10][11][12] that feature molecular flexibility or freely-rotating groups. When these molecules are photoexcited, they relax back down through molecular rotations and vibrations instead of emitting energy and are hence non-emissive.…”
Section: Introductionmentioning
confidence: 99%